2016
DOI: 10.3390/nu8030171
|View full text |Cite
|
Sign up to set email alerts
|

Low Urinary Iodine Concentrations Associated with Dyslipidemia in US Adults

Abstract: Iodine is an essential component of the thyroid hormone which plays crucial roles in healthy thyroid function and lipid metabolism. However, the association between iodine status and dyslipidemia has not been well established at a population level. We aimed to test the hypothesis that the odds of dyslipidemia including elevated total cholesterol, triglycerides, low-density lipoprotein (LDL) cholesterol and apolipoprotein B, and lowered high-density lipoprotein (HDL) cholesterol and HDL/LDL ratio are associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 49 publications
2
26
1
Order By: Relevance
“…p-Values test for homogeneity among subgroups. Some studies have reported increased odds of hypothyroidism among low UIC populations (25,38), suggesting that iodine deficiency may also be adversely related to cardiovascular outcomes (39). This study sample did not find that low UIC was associated with all-cause mortality.…”
Section: Figcontrasting
confidence: 64%
“…p-Values test for homogeneity among subgroups. Some studies have reported increased odds of hypothyroidism among low UIC populations (25,38), suggesting that iodine deficiency may also be adversely related to cardiovascular outcomes (39). This study sample did not find that low UIC was associated with all-cause mortality.…”
Section: Figcontrasting
confidence: 64%
“…Health risks have been documented not only for severe iodine deficiencies, but also as consequences of mild to moderate iodine deficiencies that are present in the US [ 5 ] and other developed countries [ 6 ]. Mild to moderate iodine deficiencies are associated with lower mental and cognitive function resulting in low IQ in children and decreased work productivity, metabolic abnormalities, thyroid dysfunction, and even goiter in adults [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The principal function of iodine acts on thyroid function, but in recent years, the role of ID in metabolism has also been gradually revealed. Analysis of data from the National Health and Nutrition Survey (NHANES) 2007-2012 found that in US adults, low urinary iodine concentration (UIC) was associated with dyslipidemia [7] and coronary artery disease [8]. Moreover, O. S. Al-Attas et al [9] reported that UIC is markedly decreased in T2DM and urinary iodine was negatively associated with insulin resistance in patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%